Association between CYP2C9 and CYP2C19 Polymorphism, Metabolism, and Neurotoxicity after Administration of Phenytoin: A Systematic Review - Mardhiani, Rizka; Harahap, Yahdiana; Wiratman, Winnugroho (Keluwih: Jurnal Kesehatan dan Kedokteran, 2023)
Abstract—Phenytoin is an antiepileptic drug (AED) metabolized by cytochrome P450 enzymes, especially by CYP2C9 (90%) and CYP2C19 (10%), where both enzymes are polymorphic so that they can undergo polymorphism and it can change the metabolic rate of the drug. Phenytoin is one of the drugs whose risk of side effects may increase due to its narrow therapeutic window of 10-20 µg/mL if the metabolism is slow. The main literature was taken from publications through the library databases in 2017 – 2021. Studies and reviews describing the metabolism, CYP2C9 and CYP2C19 polymorphisms, and neurotoxicity of phenytoin were included, and unrelated research were excluded. There were 18 of 853 articles describing CYP2C9 and CYP2C19 polymorphisms, metabolism, and neurotoxicity events associated with phenytoin used. The authors conclude that based on the results from various literature, there is an association between CYP2C9 and CYP2C19 polymorphism, metabolism, and neurotoxicity after Phenytoin administration with CYP2C9*2 and CYP2C9*3 types of polymorphisms for CYP2C9 and CYP2C19*2 and CYP2C19*3 types for CYP2C19*3 enzymes which can slow down the phenytoin metabolism and increase its concentration in serum so that the risk of causing neurotoxicity. Keywords: CYP2C9, CYP2C19,metabolism, neurotoxicity, phenytoin Abstrak—Fenitoin merupakan obat antibangkitan yang dimetabolisme oleh enzim sitokrom P450 terutama oleh CYP2C9 (90%) dan CYP2C19 (10%), dimana kedua enzim tersebut bersifat polimorfik sehingga dapat mengalami polimorfisme dan dapat mempengaruhi laju metabolisme obat. fenitoin merupakan salah satu obat yang risiko efek sampingnya dapat meningkat jika metabolismenya lambat karena jendela terapeutiknya yang sempit, yaitu 10-20 µg/mL. Literatur utama diambil dari publikasi melalui database perpustakaan tahun 2017 – 2021. Penelitian dan ulasan yang menggambarkan metabolisme, polimorfisme CYP2C9 dan CYP2C19, dan neurotoksisitas fenitoin, dan penelitian yang tidak terkait dikeluarkan. Terdapat 18 dari 853 artikel yang menjelaskan polimorfisme CYP2C9 dan CYP2C19, metabolisme, dan kejadian neurotoksisitas terkait dengan fenitoin yang digunakan. Peneliti menyimpulkan bahwa berdasarkan hasil dari berbagai literatur, terdapat hubungan antara polimorfisme, metabolisme, dan neurotoksisitas CYP2C9 dan CYP2C19 setelah pemberian fenitin dengan jenis polimorfisme CYP2C9*2 dan CYP2C9*3 untuk CYP2C9 dan CYP2C19*2 dan CYP2C19*3 jenis enzim CYP2C19*3 yang dapat memperlambat metabolisme fenitoin dan meningkatkan konsentrasinya dalam serum sehingga berisiko menyebabkan neurotoksisitas. Kata kunci: CYP2C9, CYP2C19, fenitoin, metabolisme, neurotoksisitas